ANALYSIS OF FOOD QUALITY MANAGEMENT SYSTEM IMPLEMENTATION ISO 22000 FOR PRODUCT SUSTAINABILITY IN PATIHAN LAMONGAN VILLAGE - Nurus Safa’atilllah; Ratna Handayati (UNIVERSITAS PAKUAN, 2021)
Lamongan is the largest sorghum producer in East Java. Patihan Village, Babat sub-district, is one of the sorghum-producing centers where the community already has post-harvest skills and processes sorghum into various food products. Standards are documented both the process, the origin of raw materials, as well as organoleptic factors related to quality; so that after the activity changes are obtained in the form of; the quality standard of sorghum flour produced from Patihana village will be in accordance with the criteria that have been determined together. Empowerment of sorghum processing groups through the application of the ISO 22000 food management system in a simple way becomes an urgent need so that various foods from sorghum produced are known and trusted as quality products by consumers and reach a wide market. adults and the elderly) , biscuits and so on with the specifications of the final product favored by consumers in general. The activities are designed in the form of an approach (socialization) to instill strong quality awareness, commitment and consistency in the production process. Further improvements are made together with the management of the production process, the application of traceability, sanitation, hygiene, documentation, packaging documentation, ISO wiring 22000. The method used is through qualitative descriptive research through: 1) Study Changes to the FSSC 22000 Food Safety Management System, 2) Gap Assessment and Analysis Before Improvement 3) Determination of Changes Action Recommendations, 4) Gap Analysis After Improvement. Based on this study, prior to the improvement the sorghum processing group had implemented the requirements of FSSC 22000 version 4.1 by 50%. Corrective action using risk analysis was carried out for upgrading FSSC 22000. The success of the corrective action was proven by the results of the 80.5% gap analysis. The result of the activity was a significant change. Manage the production process for the better, sanitary and hygienic and have quality documents to be implemented carried out with commitment and consistency